Revealing the controls of microbial nitrous oxide (N₂O) production and consumption using stable isotope methods - Stuchiner, Emily R., author; von Fischer, Joseph C., advisor; Baron, Jill, committee member; Cotrufo, M. Francesca, committee member; Knapp, Alan, committee member (Colorado State University. Libraries, 2021)
Of the three primary anthropogenic greenhouse gases that contribute to climate change, carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), N2O remains the most understudied. While N2O is the least abundant greenhouse gas of the three, it is also the most potent. N2O has a warming potential ~300x greater than CO2 and ~34x greater than CH4, and it is the primary stratospheric ozone depleting substance. Globally, the majority of N2O is emitted from soils through abiotic and microbial processes, but primarily through microbial metabolism. Microbes oxidize or reduce inorganic N as an energy source through different metabolic processes; they emit N2O as a byproduct of these processes. Microbes can also consume N2O by biochemically reducing it to N2, a harmless non greenhouse gas. However, the factors that regulate N2O production and consumption processes are diverse, interactive, and subject to rapid spatial and temporal changes. Drivers of N2O production and consumption include climate features, edaphic properties, and soil microbial community composition and activity. Characterizing these properties in relation to N2O flux behaviors requires a suite of measurements, and the way these factors interact to effect N2O production and consumption remain elusive. Furthermore, isotopic strategies exist to measure different N2O production processes and N2O consumption, but these strategies have been limited in their scope and capacity due to analytical constraints. Together, these challenges have limited our understanding of N2O production and consumption processes. These limitations have made it difficult to robustly disentangle the sources of N2O and understand the importance of N2O consumption in different soils. However, to curtail N2O emissions, we must be able to better understand and anticipate the drivers of N2O fluxes. In my dissertation, I seek to better understand what drives N2O production and consumption in diverse soils. In this work, I deploy innovative methods to measure different N2O production processes, and I seek to more granularly understand what controls N2O consumption. In Chapter 2 I develop a calibration algorithm for a high-throughput, novel, laser-based N2O isotopic analyzer. This allows for direct measurement of diverse microbial N2O-generating source processes. In Chapter 3 I use paired natural abundance and isotopic enrichment approaches to disentangle among N2O production processes more robustly. It will be useful for researchers to deploy paired isotopic strategies to discern more precisely which microbial process(es) are generating N2O. In Chapter 4, I shifted focus from N2O production to better understanding N2O consumption. Here, I sought to stimulate N2O consumption by amending soils with a specific blend of organic acids, and using isotope pool dilution, I learned that microbes consume more N2O when they are freed from electron donor limitation. In Chapter 5, I amended soils with different amounts of organic acids to further explore this electron donor limitation to N2O consumption. I learned that a variety of N2O flux responses can emerge from OC amendment, suggesting that perhaps our understanding of the drivers of N2O reduction are less resolved then we previously might have thought. Human activities have only exacerbated, and are poised to continue to exacerbate, N2O emissions through agricultural practices and industrial activities. There is burgeoning recognition of the importance in managing CO2 and CH4 emissions to mitigate the worst impacts of climate change, but the urgency for N2O, despite its potency and increasing atmospheric emissions, still lags. We must continue to advance understanding of the drivers of N2O production and consumption from soils, and my research makes strides to do this. This will be critical to effectively managing this highly potent greenhouse gas in a global climate that needs to make immediate, and dramatic, greenhouse gas reductions. A proposed Global Denitrification Research Network offers the potential for concerted, coordinated, and systematic N2O research to address the challenge of decreasing N2O emissions.
Keywords: managing N2O emissions; nitrous oxide (N2O); stable isotopes and isotopomers of N2O; N2O production and consumption; laser spectroscopy; soil and molecular properties